The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1978
DOI: 10.1080/03079457808418292
|View full text |Cite
|
Sign up to set email alerts
|

The response of turkey poults to experimental infection with strains ofM. gallisepticumof different virulence and withM. gallinarum

Abstract: SUMMARYIn turkey poults aged up to 28 days, a virulent S6 strain of Af. gallisepticum was recovered more frequently from more tissues for a longer time than were other strains. The virulent strain caused nervous signs and gross brain lesions in poults, and was often isolated from the brain, suggesting its neurotropism. All M. Gallisepticum strains were isolated from the synovial fluid of hocks, but swollen hocks and foot pads were seen only in poults infected with the A514 strain. It would seem, therefore, tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 13 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…It has also been shown that an Mg isolate which had not undergone laboratory passage caused airsacculitis when inoculated into 11 week old turkeys whereas the same strain, after 100 in vitro passages, did not do so (Nutor, 1969). Differences in virulence of Mg of low (2) and high (152) in vitro passage level were also shown in tracheal organ culture (Power & Jordan, 1976), in SPF chicks (Varley & Jordan, 1978a) and in turkey poults (Varley & Jordan, 1978b). Our strain of Mim had undergone only 11 in vitro passages before it was used in this study, but it was not known if this had caused any loss of natural virulence.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that an Mg isolate which had not undergone laboratory passage caused airsacculitis when inoculated into 11 week old turkeys whereas the same strain, after 100 in vitro passages, did not do so (Nutor, 1969). Differences in virulence of Mg of low (2) and high (152) in vitro passage level were also shown in tracheal organ culture (Power & Jordan, 1976), in SPF chicks (Varley & Jordan, 1978a) and in turkey poults (Varley & Jordan, 1978b). Our strain of Mim had undergone only 11 in vitro passages before it was used in this study, but it was not known if this had caused any loss of natural virulence.…”
Section: Discussionmentioning
confidence: 99%